Implementasi Isak 35 Dalam Pelaporan Keuangan Masjid Al-Hajj - Andri Widianto; Hesti Widianti (Owner : Riset dan Jurnal Akuntansi, 2023)
Mosques as public entities need good financial management. As a form of transparency and public accountability to the people. In its implementation, management is only managed simply, only recording income and expenses that occur at a certain time and submitting it as a report to the people. This form of transparency is manifested in the form of financial reports as an effort to be financially accountable to the people. This research is a field research with a qualitative descriptive approach and data was collected through direct observation, interviews with the management of the Al-Hajj Mosque. The results of the study show that the Al-Hajj Mosque keeps records based on income and expenses only without any grouping of accounts. The mosque's financial receipts come from local government subsidies, community donations and charity boxes which are distributed every Friday prayer. As for the mosque's financial expenses to finance operational expenses as well as incentives and fees. the management of the al-Hajj mosque does not know about the ISAK 35 standard, so that the presentation of the mosque's financial reports is not up to standard. The preparation of financial reports is still oriented towards the preparation of cash flow statements, where the financial reports are still only cash receipts and disbursements. Therefore researchers try to provide an overview related to ISAK 35 and implement standardized mosque financial reporting. The assets owned by the al-Hajj mosque cannot be fully described. The nominal value of the land and buildings owned is not included because this mosque is owned by the local government. The board only manages cash and cash equivalents originating from resource providers. As for debt, this mosque has no debt for the construction or operation of the mosque